AB0183 EARLY RA PATIENTS SEEN IN PRACTICE WHO HAVE CO-EXISTENT NON-ARTICULAR PAIN HAVE SIGNIFICANT WORSENING OF PROMIS® 29 DOMAIN SCORES. RESULTS FROM THE CATCH US STUDY. (2nd June 2020) - Bykerk, V.; Benson, C.; Vitone, G.; Tirpack, A.; Bartlett, S. J.; Bingham, C.
Abstract : Background: Non-articular pain (NAP) can co-exist with synovitis in RA. Its presence is associated with higher pain and worse function per legacy patient reported outcomes (PROs) both of concern to people with RA. It is not known if the presence of NAP significantly changes PROMIS 29 health domains. Objectives: To determine if co-existing NAP (both regional or widespread pain) is associated with important differences in PROMIS 29 domain scores for symptoms and impacts. Methods: Patients (pts) with early RA, were recruited from two practice settings in the Consortium of early arthritis cohorts, USA (CATCH-US) (New York and Baltimore) between Jan 2015-Dec 2019 (n=96). Data were from baseline (bl) visits; pts must have completed a body pain diagram (BPD) (CHOIR Bodymap®) and the PROMIS-29 V.1, and provided legacy PRO and clinical measures. Pts were grouped as i) no-NAP and ii) NAP based on presence of pain in non-articular regions (1-3 regions - regional, 4-5 -widespread). PROMIS 29 domain scores were compared between groups, as were related legacy PROs and clinical outcomes routinely used to assess disease activity. Data are descriptive; continuous variables were compared using t-tests. Results: Pts (n=96) had a mean age(sd) of 47.9 (14.9), 83% female, 67% white, 13% smokers, 21% obese, 82% seropositive, 51% mod/high CDAI, symptom duration 7.3 (5.4 months) and a comorbidity index (RDCI) of 0.7 (1.0). At study entry most had started RA treatments: 32% csDMARD with MTX, 22% non-MTX csDMARDs, 40% oral steroids, 13% biologics or JAKi's; 28% were treatment naive. Patients reporting NAP were more often white, smokers, obese, but did not differ otherwise. MDSJC28 was higher, mostly effected small joints, and affected regions on BPD were excluded for NAP classification. All but one (anxiety) of PROMIS 29 domain scores differed significantly between groups; similar differences were seen in legacy PRO scores and in some clinical outcomes (Table). Most clinical measures did not differ between groups. Conclusion: In this cohort of early RA patients almost 1/3 with co-existent NAP unrelated to synovitis had significantly worse legacy PRO and PROMIS scores. These data provide rationale for using generic PROMIS measures as they identify symptoms and impacts, that may be unrelated to synovitis, providing information that could improve patient-oriented care in clinical practice. Clinicians should assess for and treat NAP as part of target-based care. Reasons for (injury, mechanical, disuse) and best treatment of NAP require further research. Disclosure of Interests: Vivian Bykerk: None declared, Caroline Benson: None declared, Gregory Vitone: None declared, Aidan Tirpack: None declared, Susan J. Bartlett Consultant of: Pfizer, UCB, Lilly, Novartis, Merck, Janssen, Abbvie, Speakers bureau: Pfizer, UCB, Lilly, Novartis, Merck, Janssen, Abbvie, Clifton Bingham Grant/research support from: Bristol-Myers Squibb, Consultant of: Bristol-Myers Squibb